Age Related Gross Anatomical Changes in the Pancreas of Post-Hatched Ducks - Kumar Safi, Anil; Kumar Sinha, Manoj; Kumar Gautam, Avnish; Kumar Singh, Nirbhay (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The experiment was carried out on 40 ducks obtained from the registered duck farm of Muzaffarpur in Bihar. The ducks were divided into  four groups, each containing 10 ducks, according to their age as post-hatched (Gr-I), one month (Gr-II), 3 months (Gr-III) and 6 months  (Gr-IV) of age. The study examined the pancreas of ducks at different ages, focusing on its location ventrally posteriorly on the right  side of the median plane inside the abdominal cavity. The pancreas initially appeared light pink but turned creamy white by six months  of age. The dorsal, ventral, and splenic lobes emerged from the pancreas the day after hatching and extended longitudinally parallel  to the duodenum’s limbs. The pancreatic ventral lobe was positioned between the duodenum’s loops in group I ducks and persisted  throughout group IV ducks. The weight of the entire body of ducks increased significantly from group I to IV, with the total pancreas  weight also increasing as the ducks aged. The length and width of the entire pancreas were found to increase as the ducks’ age increased
Keywords: Age; Duck; Gross anatomy; Pancreas; Post-hatched to 6 months